ANALISIS KECERDASAN EMOSIONAL SISWA KELAS VII SMP NEGERI 2 BANGUN PURBATAHUN PEMBELAJARAN 2015/2016 - -, Sugiarti (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
AbstractÂ The purpose of this research to know the emotional Intelligence in grade VII at SMP Negeri 2 Bangun Purba in academic years 2015/2016. This is the description research. The samples are 50 students in grade VIIA and VIIB. The researcher use total sampling. To collecting the data used questionnaire. This research using description analyzes to analysis the data. The average of the research and analysis by using emotional intelligence questionnaire is good, they are 78,43%.Â Keywords : Description, Emotional, Students.